COVID-19 Pandemic: The Experience of the Emergency Department of CUF Infante Santo Hospital: Pandemia COVID-19: A Experiência do Atendimento Permanente do Hospital CUF Infante Santo - Carvalho, Gustavo de; Boquinhas, Ana Teresa (Gazeta Médica, 2020)
INTRODUCTION: The authors report the experience of adapting the Emergency Department (ED) at CUF Infante Santo Hospital (HCIS) to the pandemic of COVID-19. We review the circuits created, the approach to suspected patients and present a statistical analysis of the tests carried out for SARS-CoV-2 and infected patients. Our objective was to analyze the characteristics of patients with COVID-19, associated symptoms and severity and the necessary adaptations to face the pandemic. MATERIAL AND METHODS: The data presented corresponds to the period from March 13th to April 25th, 2020, from a database where all patients with suspected COVID-19 who resorted to the ED were registered. DISCUSSION: The results are in accordance with the data of the General Directorate of Health, but with an increase in the percentage of positive tests in relation to the national overall. There is a significant number of asymptomatic patients (13.08%). CONCLUSION: The ED diagnosed and followed-up 120 patients with SARS-CoV-2 infection, having performed a total of 1267 tests in the considered period, demonstrating the important contribution of the Portuguese private sector to the treatment of patients with COVID-19.